Resource description & access : (Published by American Library Association, 2010)
Designed for the digital world and an expanding universe of metadata users, RDA: Resource Description and Access is the new, unified cataloging standard an evolution of the cataloging principles from AACR2, with rules carried over or adapted to the RDA model. Benefits of RDA include. A structure based on the conceptual models of FRBR (functional requirements for bibliographic data) and FRAD (functional requirements for authority data) to help catalog users find the information they need more easily. A flexible framework for content description of digital resources that also serves the needs of libraries organizing traditional resources.